A composite self-repairing microcapsule, a self-repairing ball screw and a preparation method thereof

CN122974228APending Publication Date: 2026-10-27CHINA INNOVATION ACADEMY OF INTELLIGENT EQUIP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611244926.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]滚珠丝杠作为直线运动精密传动核心部件,长期承受滚珠循环交变接触应力,滚道表层及亚表面极易产生微米级疲劳微裂纹、点蚀、浅层剥落,裂纹持续扩展会造成丝杠精度丧失、异响、卡滞甚至断裂失效

Benefits of technology

本发明提供了一种包含填充胶囊和催化胶囊的复合自修复微胶囊,将该复合自修复微胶囊弥散分布于滚珠丝杠滚道亚表面区域内,在服役过程中滚道亚表面产生疲劳微裂纹时,能够自动触发复合自修复微胶囊释放修复介质,修复介质发生冶金反应实现裂纹的原位填充修复,且修复区域与母材呈冶金结合。本发明能够修复现有有机微胶囊及金属涂层无法覆盖的内部亚表面疲劳裂纹,能够使丝杠的接触疲劳寿命提升40%~65%,有效降低设备维修更换频次。同时,本发明制备工艺与现有丝杠加工产线适配,无需新增大型设备;成品滚道硬度稳定在HRC58~62范围内,硬度波动不超过±1HRC。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974228A_ABST
    Figure CN122974228A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of self-repairing technology of rolling functional component metal materials, in particular to a composite self-repairing microcapsule, a self-repairing ball screw and a preparation method thereof. The composite self-repairing microcapsule comprises a filling capsule and a catalytic capsule. The filling capsule comprises core material A and a first inner layer capsule wall and a first outer layer capsule wall which are sequentially coated on the surface of the core material A from inside to outside. The catalytic capsule comprises core material B and a second inner layer capsule wall and a second outer layer capsule wall which are sequentially coated on the surface of the core material B from inside to outside. The core material A is a Fe-Sn-B alloy, and the core material B comprises a Fe-Cr-Mn alloy and rare earth yttrium catalytic particles. The first inner layer capsule wall and the second inner layer capsule wall independently comprise a nickel-iron alloy layer, and the first outer layer capsule wall and the second outer layer capsule wall independently comprise a titanium carbonitride layer. The composite self-repairing microcapsule can automatically repair the fatigue microcracks generated on the subsurface of the raceway during service in situ, and effectively improve the contact fatigue life of the screw.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of self-healing technology for rolling functional component metal materials, and more specifically, to a composite self-healing microcapsule, a self-healing ball screw, and a method for preparing the same. Background Technology

[0002] As a core component of precision linear motion transmission, ball screws are subjected to alternating contact stress from the rolling balls over long periods. The raceway surface and subsurface are highly susceptible to micron-level fatigue microcracks, pitting, and shallow spalling. Continued crack propagation can lead to loss of screw precision, abnormal noise, jamming, and even breakage. Current conventional methods for extending screw life focus on material modification and surface strengthening: spheroidizing annealing refines the matrix structure, induction hardening increases surface hardness, and nitriding / diamond-like coating enhances wear resistance. However, these methods only delay crack initiation and cannot repair existing internal micro-damage. Once subsurface cracks appear, the entire screw must be replaced, resulting in high operating costs and significant downtime losses.

[0003] Current self-healing technologies for materials mainly include microcapsules and metal coatings, but all of them have inherent limitations in adapting to carbon steel ball screws. Organic polymer microcapsules: The capsule wall and repair core material are both organic materials such as epoxy resin and silicone resin, which can withstand temperatures not exceeding 400℃. At high temperatures, the organic capsules decompose and fail. Moreover, the large particles of commercial microcapsules, when embedded in the steel matrix, will sever the continuous martensitic structure, reduce the contact fatigue strength and hardness of the raceway, and can only be used for surface coating of parts, and cannot be embedded in the interior of the metal matrix. After repair, it relies on organic bonding. Under friction conditions of 80-180℃, the resin softens and the repair interface is easy to fall off.

[0004] Metal coating: only covers the outer surface of the parts. The high-incidence area of ​​screw failure is the subsurface 0-2mm below the raceway. Internal cracks cannot contact the repair medium, resulting in a blind spot in the repair range.

[0005] Existing patents related to ball screws mainly focus on optimizing heat treatment processes, surface coatings, and improving ball return structures. No related technical solutions have been found that involve dispersing self-healing microcapsules within a carbon steel substrate to achieve in-situ repair of subsurface cracks during service. Therefore, this invention provides a composite self-healing microcapsule, a self-healing ball screw, and a method for preparing the same, to solve at least one of the technical problems existing in the prior art. Summary of the Invention

[0006] The purpose of this invention is to provide a composite self-healing microcapsule, a self-healing ball screw, and a method for preparing the same. The composite self-healing microcapsule is dispersed within the subsurface region of the ball screw raceway. When fatigue microcracks develop on the raceway subsurface during service, the composite self-healing microcapsule automatically releases a repair medium. This repair medium undergoes a metallurgical reaction to achieve in-situ filling and repair of the cracks. Furthermore, the repaired area exhibits a metallurgical bond with the base material, thereby improving the contact fatigue life of the ball screw and reducing the frequency of equipment maintenance and replacement.

[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A composite self-healing microcapsule includes a filling capsule and a catalytic capsule. The filling capsule includes a core material A and a first inner capsule wall and a first outer capsule wall that are sequentially covered on the surface of the core material A from the inside out. The catalytic capsule includes a core material B and a second inner capsule wall and a second outer capsule wall that are sequentially covered on the surface of the core material B from the inside out. The core material A is an Fe-Sn-B alloy, and the core material B includes an Fe-Cr-Mn alloy and rare earth yttrium catalyst particles; the first inner capsule wall and the second inner capsule wall each independently include an iron-nickel alloy layer, and the first outer capsule wall and the second outer capsule wall each independently include a titanium carbonitride layer.

[0008] Preferably, the Fe-Sn-B alloy comprises, by mass percentage: Fe 40%~45%, Sn 38%~42%, and B 13%~22%.

[0009] Preferably, the Fe-Cr-Mn alloy comprises 40%~46% Fe, 40%~44% Cr, and 10%~20% Mn by mass percentage.

[0010] Preferably, in the core material B, the mass fraction of the rare earth yttrium catalyst particles is 0.8% to 1.2%.

[0011] Preferably, by mass percentage, the first inner bladder wall and the second inner bladder wall independently comprise 62%~68% Fe and 32%~38% Ni, respectively.

[0012] Preferably, the thickness of the first inner capsule wall and the second inner capsule wall are each independently 1~3µm.

[0013] Preferably, the thicknesses of the first outer capsule wall and the second outer capsule wall are each independently 500~600 nm.

[0014] Preferably, the particle size of the filling capsule and the catalytic capsule are each independently 8~15µm.

[0015] Preferably, the mass ratio of the filling capsule to the catalytic capsule is 1:1 to 1.5:1.

[0016] A self-healing ball screw, wherein composite self-healing microcapsules as described in any of the preceding embodiments are diffusely distributed in a substrate area not exceeding 2 mm below the raceway surface of the ball screw.

[0017] Preferably, the base material of the ball screw is medium carbon steel or high carbon steel.

[0018] The method for preparing the self-healing ball screw according to any one of the foregoing embodiments includes the following steps: S1. Take a steel-based light rod raw material, coat its surface with a mixture of composite self-healing microcapsules and carbon steel binder, and then perform multiple warm rolling composites to embed the composite self-healing microcapsules into the surface matrix of the light rod raw material to obtain a composite billet; S2. The composite billet is preheated to obtain a pretreated billet; S3. Perform induction hardening and tempering on the pretreated billet; S4. The tempered blank is formed to create a spiral raceway; then it is finished to obtain the self-healing ball screw; the composite self-healing microcapsules are still diffusely distributed in the matrix area no more than 2 mm below the surface of the raceway of the self-healing ball screw.

[0019] Preferably, in step S1, the thickness of each pass of the hot drawing coating of the mixture is 650~700µm.

[0020] Preferably, in step S1, the mass ratio of the composite self-healing microcapsule to the carbon steel adhesive is 4:1 to 3:1.

[0021] Preferably, in step S1, the temperature of the warm rolling is 720~850℃, the number of warm rolling passes is 3~4, and the reduction rate per pass is ≤12%.

[0022] Preferably, in step S2, the preheating process is selected according to the material of the steel substrate billet: when the steel substrate is high carbon steel, spheroidizing annealing is performed; when the steel substrate is medium carbon steel, quenching and tempering is performed.

[0023] Preferably, in step S3, the induction hardening temperature is 880~910℃, the tempering temperature is 160~200℃, and the tempering time is 2~4h.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a composite self-healing microcapsule comprising a filling capsule and a catalytic capsule. This composite self-healing microcapsule is dispersed within the subsurface region of a ball screw raceway. During service, when fatigue microcracks develop on the raceway subsurface, the composite self-healing microcapsule automatically releases a repair medium. The repair medium undergoes a metallurgical reaction, achieving in-situ filling and repair of the cracks, and the repaired area exhibits a metallurgical bond with the base material. This invention can repair internal subsurface fatigue cracks that cannot be covered by existing organic microcapsules and metal coatings, increasing the contact fatigue life of the ball screw by 40%–65% and effectively reducing the frequency of equipment maintenance and replacement. Furthermore, the manufacturing process of this invention is compatible with existing ball screw processing lines, requiring no additional large-scale equipment; the hardness of the finished raceway is stable within the range of HRC58–62, with hardness fluctuations not exceeding ±1 HRC. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the structure of the filling capsule and the catalytic capsule in the composite self-healing microcapsule provided in an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a self-healing ball screw provided in an embodiment of the present invention. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0028] like Figure 1 As shown, a first aspect of the present invention provides a composite self-healing microcapsule, comprising a filling capsule and a catalytic capsule. The filling capsule comprises a core material A and a first inner capsule wall and a first outer capsule wall sequentially covering the surface of the core material A from the inside out. The catalytic capsule comprises a core material B and a second inner capsule wall and a second outer capsule wall sequentially covering the surface of the core material B from the inside out. Core material A is an Fe-Sn-B alloy, and core material B includes an Fe-Cr-Mn alloy and rare earth yttrium catalyst particles; the first inner capsule wall and the second inner capsule wall each independently include an iron-nickel alloy layer, and the first outer capsule wall and the second outer capsule wall each independently include a titanium carbonitride layer.

[0029] The composite self-healing microcapsules provided by this invention include a filling capsule and a catalytic capsule. The filling capsule contains a Fe-Sn-B low-melting-point alloy (melting point 160~200℃), which is solid at room temperature and transforms into a liquid state upon rupture due to frictional heat. It fills 0.1~20μm microcracks and shallow pitting corrosion using capillary force. Upon rupture of the catalytic capsule, nano-Fe-Cr-Mn powder and rare earth yttrium particles are released. The liquid-phase Fe-Sn-B and Fe-Cr-Mn particles react in the presence of the rare earth yttrium catalytic particles to form a Fe-Sn-B-Cr-Mn multi-element eutectic liquid phase. This multi-element eutectic liquid phase spontaneously penetrates deep into the crack and into subsurface pitting corrosion, rapidly filling all voids. Fe atoms in the carbon steel matrix on both sides of the crack synchronously diffuse towards the interface of the repair liquid phase. Fe and Cr elements in the repair liquid phase penetrate into the surface of the parent material, forming a metallurgical interdiffusion transition layer, thus achieving crack filling and repair. Neither filler capsules nor catalytic capsules alone can form Fe-Sn-B-Cr-Mn multi-element eutectic liquid, making it difficult to effectively improve the fatigue life of ball screws.

[0030] In this invention, both the filling capsule and the catalytic capsule possess a double-layer gradient composite capsule wall structure. The outer capsule wall is a brittle titanium carbonitride layer, and the inner capsule wall is a ductile Fe-Ni alloy layer. The outer capsule wall is a brittle layer with high hardness and low toughness, ensuring that the shear stress at the crack tip can trigger capsule rupture. The inner capsule wall controls the amount of core material released, with the unruptured portion remaining in the matrix, enabling multiple repairs. The two capsule walls work together to ensure both timely response and effective repair of cracks, and to achieve multiple repairs of the same damaged area. If only the outer capsule wall is used, the core material is completely released after the first trigger, losing the ability to repair multiple times. If only the inner capsule wall is used, the tearing effect is limited, with only a portion of the capsule releasing the core material, making it difficult to achieve complete crack repair.

[0031] The self-healing microcapsules of this invention require the synergistic effect of two components—a filling capsule and a catalytic capsule—as well as a double-layered capsule wall structure consisting of an inner and outer capsule wall, to effectively achieve multiple repairs of the same damaged area, thereby significantly improving the contact fatigue life of the lead screw.

[0032] In some specific embodiments of the present invention, the Fe-Sn-B alloy comprises, by mass percentage: Fe 40%~45%, Sn 38%~42%, and B 13%~22%. Typically, but not limitingly, for example, in the Fe-Sn-B alloy, the mass percentage of Fe can be any one value or a range of any two values ​​from 40%, 42%, 44%, and 45%; the mass percentage of Sn can be any one value or a range of any two values ​​from 38%, 39%, 40%, 41%, and 42%; and the mass percentage of B can be any one value or a range of any two values ​​from 13%, 15%, 18%, 20%, and 22%.

[0033] In some specific embodiments of the present invention, the Fe-Cr-Mn alloy comprises, by mass percentage, 40%~46% Fe, 40%~44% Cr, and 10%~20% Mn. Typically, but not limitingly, for example, in the Fe-Cr-Mn alloy, the mass percentage of Fe can be any one of 40%, 42%, 44%, or a range of any two of these values; the mass percentage of Cr can be any one of 40%, 41%, 42%, 43%, or 44% or a range of any two of these values; and the mass percentage of Mn can be any one of 10%, 12%, 15%, 18%, or 20% or a range of any two of these values.

[0034] In some specific embodiments of the present invention, both the Fe-Cr-Mn alloy and the rare earth yttrium catalyst particles are nanoparticles, and the average particle size of the powder is independently 200~500nm. For example, it can be any point value or a range of any two point values ​​among 200nm, 300nm, 400nm, and 500nm.

[0035] In some specific embodiments of the present invention, the mass fraction of rare earth yttrium catalyst particles in core material B is 0.8% to 1.2%, for example, it can be any single value or a range of any two values ​​from 0.8%, 0.9%, 1%, 1.1%, to 1.2%. Rare earth yttrium acts as an interface activator, capable of removing trace oxide films from the crack walls of liquid Fe-Sn-B alloy and carbon steel, and from the surface of Fe-Cr-Mn powder, eliminating interfacial reaction barriers, and simultaneously reducing the atomic diffusion activation energy between the Fe-Sn-B liquid phase and the Fe-Cr-Mn solid phase, allowing the metallurgical reaction to continue within the frictional heat range of 120~180℃.

[0036] In some specific embodiments of the present invention, the first inner layer and the second inner layer of the capsule independently comprise, by mass percentage, 62% to 68% Fe and 32% to 38% Ni. Typically, but not limitingly, for example, the mass percentage of Fe in the first and second inner layers of the capsule can be any single value or a range of any two values ​​from 62%, 64%, 66%, and 68%; the mass percentage of Ni can be any single value or a range of any two values ​​from 32%, 34%, 36%, and 38%.

[0037] In some specific embodiments of the present invention, the thicknesses of the first inner capsule wall and the second inner capsule wall are independently 1~3µm, for example, they can be any one value or a range of any two points from 1µm, 1.5µm, 2µm, 2.5µm, to 3µm.

[0038] In some specific embodiments of the present invention, the thickness of the first outer capsule wall and the second outer capsule wall are independently 500~600nm, for example, they can be any one value or a range of any two values ​​among 500nm, 520nm, 550nm, 580nm, and 600nm.

[0039] In some specific embodiments of the present invention, the particle size of the filling capsule and the catalyst capsule are independently 8~15µm, for example, they can be any one value or a range of any two values ​​among 8µm, 10µm, 12µm, and 15µm.

[0040] In some specific embodiments of the present invention, the mass ratio of the filling capsule to the catalyst capsule is 1:1 to 1.5:1. For example, it can be any one value or a range of any two values ​​from 1:1, 1.2:1, 1.4:1, 1.5:1.

[0041] In some specific embodiments of the present invention, the preparation method of the composite self-healing microcapsules includes the following steps: Iron-nickel alloy was deposited on the surface of core material A by vapor deposition to form the first inner capsule wall. Then, a titanium carbonitride brittle layer (i.e. the first outer capsule wall) was formed by plasma spraying. The filler capsules with the required particle size were obtained by sieving. A nickel-iron alloy was deposited on the surface of core material B using vapor deposition to form the second inner capsule wall. Then, a brittle titanium carbonitride layer (i.e., the second outer capsule wall) was formed by plasma spraying. The catalytic capsules of the desired particle size were obtained by sieving. The filler capsule and the catalyst capsule are mixed in a certain proportion to obtain a composite self-healing microcapsule.

[0042] like Figure 2As shown, a second aspect of the present invention provides a self-healing ball screw, wherein composite self-healing microcapsules as described in any of the foregoing embodiments are diffusely distributed in a matrix region not exceeding 2 mm below the raceway surface of the ball screw.

[0043] During the service life of self-healing ball screws, the mechanism by which the filling capsule and catalytic capsule react in situ to fill and repair cracks is as follows: When the lead screw operates under frictional heat conditions of 120~180℃, fatigue microcracks develop on the subsurface of the raceway. The filler capsules and catalytic capsules (uniformly mixed) located within the 0~2mm self-healing layer on the subsurface respond to damage. The outer layer of both types of capsules is a brittle TiCN nanolayer with low shear strength; the concentrated shear stress field formed at the crack tip can directly tear the brittle outer shell. The inner layer is an Fe-Ni alloy shell with good plasticity, cracking only locally, allowing the internal core material to be released. Undamaged capsules remain in the matrix, enabling multiple repairs in the same damaged area.

[0044] The high-speed rolling of the ball bearings generates continuous frictional heat, maintaining a stable local temperature of 120-180℃ in the raceway. Upon rupture of the filling capsule, a solid Fe-Sn-B alloy is released, which melts into a low-viscosity liquid metal under frictional heat, exhibiting good wettability to the carbon steel matrix. Simultaneously, upon rupture of the catalytic capsule, nano-Fe-Cr-Mn powder and rare-earth yttrium particles are released. The liquid Fe-Sn-B encapsulates the nano-Fe-Cr-Mn particles, with Sn and B elements rapidly diffusing into the Fe-Cr-Mn powder, while Fe, Cr, and Mn dissolve in the liquid alloy in opposite directions, forming a Fe-Sn-B-Cr-Mn multi-element eutectic liquid phase.

[0045] Under capillary action, this multi-element eutectic liquid phase spontaneously penetrates into the depths of cracks and subsurface pits. The narrower and deeper the crack, the stronger the capillary driving force, allowing penetration to deep subsurface microcracks up to 2 mm from the raceway surface. Simultaneously, Fe atoms in the carbon steel matrix on both sides of the crack diffuse towards the interface of the repair liquid phase, while Fe and Cr elements in the repair liquid phase penetrate into the surface of the base material, forming a metallurgical interdiffusion transition layer. The solidified metal repair layer completely fills the crack cavity, blocking stress transmission at the crack tip and thus preventing the microcracks from propagating deeper.

[0046] As an interface activator, rare earth yttrium can preferentially remove trace oxide films from the crack walls of liquid Fe-Sn-B alloy and carbon steel, as well as from the surface of Fe-Cr-Mn powder, eliminating interfacial reaction barriers. Simultaneously, it lowers the atomic diffusion activation energy between the Fe-Sn-B liquid phase and the Fe-Cr-Mn solid phase, allowing the metallurgical reaction to continue within the frictional heat range of 120~180℃. If a short shutdown causes a temperature drop and the reaction to temporarily slow down, restarting and reheating will allow the metallurgical bonding to continue without midway failure. If new cracks subsequently form, the surrounding undamaged filler capsules and catalyst capsules can repeat the above process, achieving multiple progressive repairs.

[0047] In some specific embodiments of the present invention, the base material of the ball screw is medium carbon steel (such as 4150H, 55# steel, etc.) or high carbon steel (such as GCr15).

[0048] A third aspect of the present invention provides a method for preparing a self-healing ball screw according to any one of the foregoing embodiments, comprising the following steps: S1. Take a steel-based light rod raw material, coat its surface with a mixture of composite self-healing microcapsules and carbon steel binder, and then perform multiple warm rolling composites to embed the composite self-healing microcapsules into the surface matrix of the light rod raw material to obtain a composite billet; S2. The composite billet is preheated to obtain a pretreated billet; S3. Perform high-frequency induction hardening and low-temperature tempering on the obtained pretreated billet; S4. The tempered blank is shaped and processed, including turning the outer diameter and milling the spiral raceway to form the spiral raceway; after the shaped process, it is finished (semi-finish grinding and finish grinding) to obtain the self-healing ball screw; composite self-healing microcapsules are dispersed in the matrix area not exceeding 2mm below the surface of the self-healing ball screw raceway.

[0049] The preparation process of this invention is based on the modification of existing hot rolling, preheating treatment (spheroidizing annealing or tempering), and induction hardening production lines, without the need for new large-scale equipment, and the increase in industrialization cost is less than 12%.

[0050] In some specific embodiments of the present invention, in step S1, the thickness of the mixture for each pass of temperature drawing coating is 650~700µm. For example, it can be any one value or a range of any two values ​​among 650µm, 660µm, 680µm, and 700µm.

[0051] In some specific embodiments of the present invention, the mass ratio of the composite self-healing microcapsules to the carbon steel binder in the mixture of step S1 is 4:1 to 3:1. For example, it can be any one value or a range of any two values ​​from 4:1, 3.8:1, 3.5:1, 3.2:1, to 3:1. As an example, the carbon steel binder can be at least one of phenolic resin, polyurethane acrylate, and epoxy acrylate.

[0052] In some specific embodiments of the present invention, in step S1, the temperature of the warm rolling is 720~850℃, for example, it can be any one value or a range of any two values ​​among 720℃, 750℃, 800℃, and 850℃; the number of warm rolling passes is 3~4 passes, and the reduction rate of a single pass is ≤12%, for example, it can be any one value or a range of any two values ​​among 12%, 10%, 8%, and 6%.

[0053] In some specific embodiments of the present invention, in step S2, the preheating process is selected according to the material of the steel substrate billet: when the steel substrate is high carbon steel, spheroidizing annealing is performed; when the steel substrate is medium carbon steel, quenching and tempering is performed.

[0054] As an example, the spheroidizing annealing process includes: holding the composite billet at 780°C for 3 hours, slowly cooling it to 680°C at a rate of 20°C / h and holding it at 680°C for 3 hours, and finally cooling it to 600°C at a rate of 20°C / h before removing it from the furnace, thus completing the spheroidization of the matrix and ensuring that the microcapsule structure is intact and leak-free.

[0055] As an example, the tempering process includes: heating from room temperature to 550°C at 10°C / min, holding at that temperature for 0.5h, then heating to 850°C at 10°C / min, holding at that temperature for 3h, followed by oil cooling, then heating to 650°C at 10°C / min, holding at that temperature for 3h, furnace cooling to 500°C, and finally air cooling after removal from the furnace.

[0056] In some specific embodiments of the present invention, in step S3, the induction hardening temperature is 880~910℃, for example, it can be any one value or a range of any two values ​​among 880℃, 890℃, 900℃, and 910℃; the tempering temperature is 160~200℃, for example, it can be any one value or a range of any two values ​​among 160℃, 170℃, 180℃, 190℃, and 200℃; and the tempering time is 2~4h, for example, it can be any one value or a range of any two values ​​among 2h, 2.5h, 3h, 3.5h, and 4h.

[0057] The following detailed description of some embodiments of the present invention is provided in conjunction with specific examples. Unless otherwise specified, all raw materials used in the embodiments are commercially available.

[0058] Example 1 (1) Preparation of composite self-healing microcapsules Iron-nickel alloy inner capsule walls were deposited on the raw material surfaces of core material A and core material B by vapor deposition, and titanium carbonitride outer capsule walls were formed by plasma spraying. Filled capsules and catalytic capsules with a diameter of 8-12 μm were obtained by sieving and mixed at a 1:1 mass ratio for later use. The inner capsule walls of both the filled and catalytic capsules were 62%Fe-32%Ni alloy layers with a thickness of 2 μm; the outer capsule walls were both TiCN brittle layers with a thickness of 500 nm. Core material A was a 45%Fe-42%Sn-13%B low-melting-point alloy, and core material B consisted of 45%Fe-42%Cr-13%Mn alloy powder with an average particle size of 300 nm and rare earth yttrium nanoparticles with an average particle size of 400 nm. The mass fraction of rare earth yttrium in core material B was 0.8%.

[0059] (2) Preparation of self-healing ball screw S1. The base blank is made of φ40mm GCr15 bar. The surface is sprayed with a mixture of composite self-healing microcapsules and carbon steel binder (phenolic resin) (the mass ratio of composite self-healing microcapsules to carbon steel binder is 4:1). The coating thickness is 700µm per pass. After 3 passes of warm rolling at 720℃, the single pass reduction rate is 10%, and a 2mm self-healing modified layer is formed to obtain the composite blank. S2. Spheroidizing annealing treatment of composite billet: hold at 780℃ for 3h, slowly cool to 680℃ at a rate of 20℃ / h and hold for 3h, and finally cool to 600℃ at a rate of 20℃ / h and remove from the furnace. The matrix is ​​spheroidized and the microcapsules are intact and leaking, thus obtaining the pretreated billet. S3. Perform induction hardening on the pretreated billet at 890℃ and tempering at 180℃ for 2 hours; S4. The tempered billet is formed by rough machining of the spiral raceway; the finished self-healing ball screw is obtained by finish machining; the hardness of the finished raceway is HRC60~62.

[0060] In this case, the amount of material removed during rough machining of the spiral raceway is <0.3 mm, the amount removed during finishing grinding is <0.1 mm, and the composite self-healing microcapsules are still diffusely distributed in the subsurface layer of the raceway (same as other embodiments and comparative examples). Performance testing: Alternating contact fatigue testing machine with 10 cycles of loading 7 In a typical GCr15 lead screw, a 0.015mm subsurface crack appeared on the raceway. In this embodiment, the lead screw developed an equivalent crack and then self-healed automatically, completely closing the crack. The hardness was HRC59~60, and the cycle continued until 1.65×10⁻⁶. 7 New damage only occurs once, and fatigue life is increased by 65%; cracks can be repaired even if they occur four times in the same location.

[0061] Example 2 (1) Preparation of composite self-healing microcapsules The microcapsule particle size was controlled at 10~15μm, and the other components of the capsule wall, core material ratio and preparation process were the same as in Example 1.

[0062] (2) Preparation of self-healing ball screw S1. The base material is 4150H bar, and the composite process is the same as in Example 1 to obtain the composite material; S2. The composite billet is subjected to quenching and tempering treatment: the temperature is increased from room temperature to 550℃ at 10℃ / min and held for 0.5h, then increased to 850℃ at 10℃ / min and held for 3h, followed by oil cooling, then increased to 650℃ at 10℃ / min and held for 3h, then furnace cooled to 500℃ and air cooled to obtain the pretreated billet; S3. Perform induction hardening on the pretreated billet at 880℃ and tempering at 200℃ for 2 hours; S4. The tempered billet is formed by rough machining of the spiral raceway; the finished self-healing ball screw is obtained by finish machining; the hardness of the finished raceway is HRC60~61.

[0063] Operating condition test: After continuous high-temperature and high-speed operation at 120℃, pitting microcracks appeared on the raceway and automatically repaired themselves. The repaired interface showed no peeling, and the cycle continued to 1.55×10. 7 New damage only occurs after the first time, and the fatigue life is increased by 55% compared to ordinary 4150H ball screws; it can be repaired even if the same crack occurs 4 times in the same location.

[0064] Comparative Example 1 Comparative Example 1 is similar to Example 1, except that the filled capsule and the catalytic capsule have only a TiCN outer capsule wall and no Fe-Ni alloy inner capsule wall; the remaining process steps and condition parameters are the same as those in Example 1.

[0065] Because there is no inner iron-nickel alloy shell for plastic protection, the internal core material of the capsule is completely released after the first repair, and the same damaged area loses its ability to repair multiple times, resulting in a fatigue life increase of only 25%.

[0066] Comparative Example 2 Comparative Example 2 is similar to Example 1, except that the filled capsule and the catalytic capsule have only an inner Fe-Ni alloy capsule wall and no TiCN outer capsule wall; the remaining process steps and condition parameters are the same as those in Example 1.

[0067] Due to the absence of an outer brittle layer, the stress at the crack tip has a limited effect on tearing the inner Fe-Ni alloy layer. Only a portion of the core material inside the capsule is fully released, failing to achieve complete self-repair of microcracks, and the fatigue life is only improved by 20%.

[0068] Comparative Example 3 Comparative Example 3 is similar to Example 1, except that the self-healing microcapsules only have core material B and no core material A; that is, the self-healing microcapsules are only catalytic capsules; the remaining process steps and condition parameters are the same as those in Example 1.

[0069] Because the Fe-Sn-B-Cr-Mn multi-element eutectic liquid phase could not be formed, the Fe-Cr-Mn powder particles alone could not form a metallurgical interdiffusion transition layer, thus failing to achieve complete self-repair of microcracks, and the fatigue life was only improved by 8%.

[0070] Comparative Example 4 Comparative Example 4 is similar to Example 1, except that the self-healing microcapsules only have core material A and no core material B; that is, the self-healing microcapsules are only filler capsules; the remaining process steps and condition parameters are the same as those in Example 1.

[0071] Because the Fe-Sn-B-Cr-Mn multi-element eutectic liquid phase cannot be formed, only the Fe-Sn-B alloy melts into a low-viscosity liquid metal, and there is no rare earth yttrium interfacial activator effect, the fatigue life is only improved by 5%.

[0072] Comparative Example 5 Comparative Example 5 is similar to Example 1, except that 10μm epoxy resin microcapsules are used as self-healing microcapsules; the remaining process steps and condition parameters are the same as those in Example 1.

[0073] After spheroidizing annealing at 780℃, the organic capsules are completely carbonized and decomposed, and have no self-healing function; the carbonization and decomposition products at 0~2mm cause the sample hardness to decrease by about 7HRC and the contact fatigue strength to decrease by about 60%, making it unsuitable for lead screw machining.

[0074] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. A composite self-healing microcapsule, characterized in that, The product includes a filled capsule and a catalytic capsule. The filled capsule includes a core material A and a first inner capsule wall and a first outer capsule wall that are sequentially covered on the surface of the core material A from the inside out. The catalytic capsule includes a core material B and a second inner capsule wall and a second outer capsule wall that are sequentially covered on the surface of the core material B from the inside out. The core material A is an Fe-Sn-B alloy, and the core material B includes an Fe-Cr-Mn alloy and rare earth yttrium catalyst particles; the first inner capsule wall and the second inner capsule wall each independently include an iron-nickel alloy layer, and the first outer capsule wall and the second outer capsule wall each independently include a titanium carbonitride layer.

2. The composite self-healing microcapsule according to claim 1, characterized in that, The Fe-Sn-B alloy comprises, by mass percentage: Fe 40%~45%, Sn 38%~42%, and B 13%~22%.

3. The composite self-healing microcapsule according to claim 1, characterized in that, The Fe-Cr-Mn alloy comprises 40%~46% Fe, 40%~44% Cr, and 10%~20% Mn by mass percentage.

4. The composite self-healing microcapsule according to claim 1, characterized in that, In the core material B, the mass fraction of the rare earth yttrium catalyst particles is 0.8%~1.2%.

5. The composite self-healing microcapsule according to claim 1, characterized in that, By mass percentage, the first inner bladder wall and the second inner bladder wall independently comprise 62%~68% Fe and 32%~38% Ni, respectively.

6. The composite self-healing microcapsule according to claim 1, characterized in that, It meets at least one of the following characteristics: (1) The thickness of the first inner capsule wall and the second inner capsule wall are independently 1~3µm; (2) The thickness of the first outer capsule wall and the second outer capsule wall are independently 500~600nm; (3) The particle size of the filling capsule and the catalyst capsule are independently 8~15µm; (4) The mass ratio of the filling capsule to the catalyst capsule is 1:1 to 1.5:

1.

7. A self-healing ball screw, characterized in that, The composite self-healing microcapsules according to any one of claims 1 to 6 are diffusely distributed in a matrix area not exceeding 2 mm below the raceway surface of the ball screw.

8. The self-healing ball screw according to claim 7, characterized in that, The base material of the ball screw is medium carbon steel or high carbon steel.

9. The method for preparing the self-healing ball screw according to claim 7 or 8, characterized in that, Includes the following steps: S1. Take a steel-based light rod raw material, coat its surface with a mixture of composite self-healing microcapsules and carbon steel binder, and perform multiple warm rolling composites to embed the composite self-healing microcapsules into the surface matrix of the light rod raw material to obtain a composite billet; S2. The composite billet is preheated to obtain a pretreated billet; S3. Perform induction hardening and tempering on the pretreated billet; S4. The tempered blank is formed to create a spiral raceway; then it is finished to obtain the self-healing ball screw; the composite self-healing microcapsules are dispersed in a matrix area not exceeding 2mm below the surface of the raceway of the self-healing ball screw.

10. The method for preparing a self-healing ball screw according to claim 9, characterized in that, It meets at least one of the following characteristics: (1) In step S1, the thickness of the mixture in each heat-draw coating is 650~700µm; (2) In step S1, the mass ratio of the composite self-healing microcapsule to the carbon steel adhesive is 4:1 to 3:1; (3) In step S1, the temperature of the warm rolling is 720~850℃, the number of warm rolling passes is 3~4, and the reduction rate of a single pass is ≤12%; (4) In step S2, the preheating process is selected according to the material of the steel substrate billet: when the steel substrate is high carbon steel, spheroidizing annealing is performed; when the steel substrate is medium carbon steel, quenching and tempering is performed. (5) In step S3, the induction hardening temperature is 880~910℃, the tempering temperature is 160~200℃, and the tempering time is 2~4h.